The Role of Speech Therapy in Patients Who Underwent Laryngeal Microsurgery due to Phonotraumatic Lesions and Lesions Unrelated to Phonotrauma - Macedo,Claudia de Assis Corrêa de (2014)
Introduction The role of the speech-language pathology in the multiprofessional team dealing with laryngology and the voice has been recognized for a long time. Scientific studies in this field recommend therapies for laryngeal microsurgeries; few of the studies, however, effectively evaluate the result of postoperative speech therapy. Objective To compare speech therapy evaluation and treatment among patients with phonotraumatic lesions and patients with lesions unrelated to phonotrauma who underwent laryngeal microsurgery. Methods This study was performed at IPO Hospital (Paranaense Institute of Otorhinolaryngology, Curitiba, Paraná, Brazil) between February 2010 and February 2011. Of 254 patients who underwent laryngeal microsurgery, 208 patients were included in the study and divided in two groups: group A with phonotraumatic lesions (n = 131) and group B with lesions unrelated to phonotrauma (n = 77). The number of sessions and the functional result after speech therapy were evaluated. Results The number of postoperative phonotherapy sessions after microsurgery was up to 10 sessions in 89.31% and 87.71% for groups A and B, respectively. Phonotherapy treatment showed a better functional evolution in group A (92.37%). Conclusion A significant difference was observed only in functional evolution, which was better in the group with phonotraumatic lesions (p < 0.0001).